People living in poverty and their relationship to local church communities: An exploratory qualitative study in Mechelen, Belgium - Dillen, Annemie (HTS teologiese studies, 2016)
Much literature on church and poverty issues takes the church as the actor and people living in poverty as the acted upon, those who have to receive care or who will benefit from the church’s diaconal action. Not much is known about experiences of the church and the religion of people living in poverty themselves. The aim of this article is threefold: (1) To learn more about possible difficulties, also possibilities, for participation of people living in poverty in Catholic parishes in Flanders; (2) To give a voice to people living in poverty, to help them to express their ‘ordinary theology’ (Astley 2002) and to make their experiences visible to a broader ecclesial audience; (3) To discuss the ecclesial experiences of people living in poverty and people who know their experiences quite well, in light of church documents.This article presents the results of an exploratory qualitative study in Mechelen, a medium-tolarge city in Flanders, Belgium. We present the results of semi-structured interviews with 20 participants – 7 caregivers and 13 people living in poverty.We found both pragmatic difficulties and more religious difficulties for participation in parishes, named by people living in poverty, as well as by (voluntary and professional) caregivers. Pragmatic difficulties are, for example, mobility or time (in relation to working hours on Saturday/Sunday). More religious-related difficulties concern the doubts about God in relation to their own suffering, aspects of the moral teachings of the church (e.g. about homosexuality) and questions about the Eucharist itself, experienced in a non-satisfactory way. More positive experiences concern the silence or rest people experience in the church or the experience of a community. We discuss findings relating to experiences of ‘inclusion’ of people living in poverty within church communities and more private religious practices, named by people living in poverty.In a next step, we compare these results with other empirical research. Finally, we discuss what it can mean to be a ‘church of the poor’ and what ‘friendship with the poor’ might be and how this concept can be evaluated.